ccf-mtDNA as a Potential Link Between the Brain and Immune System in Neuro-Immunological Disorders - Gambardella, Stefano; Limanaqi, Fiona; Ferese, Rosangela; Biagioni, Francesca; Campopiano, Rosa; Centonze, Diego; Fornai, Francesco (Frontiers in Immunology, 2019)
Fragments of mitochondrial DNA (mtDNA) are released outside the cell and they appear to persist in extracellular ﬂuids as circulating, cell-free, mtDNA (ccf-mtDNA). When compared to nuclear DNA, such a double stranded mtDNA is more resistant to nuclease degradation. In fact, it is stable extracellularly where it can be detected in both plasma and cerebrospinal fluid (CSF), here acting as a potential biomarker in various disorders. In neurological diseases (Alzheimer's disease, Parkinson's disease and end-stage progressive Multiple Sclerosis), a decreased amount of CSF ccf-mtDNA is related with progressive cell dysfunction. This suggests an alteration in neuronal mtDNA levels (mtDNA replication, degradation and depletion) in vulnerable brain regions at early stages of neurodegeneration leading to reduced mtDNA release, which takes place before actual cell death occurs. On the other hand, elevated CSF ccf-mtDNA levels are reported in acute phases of relapsing-remitting Multiple Sclerosis (RRMS). This occurs during acute inﬂammation, which anticipates the neurodegenerative process. Thus, an increase in inﬂammatory cells in the affected regions is expected to add on mtDNA release into the CSF. In addition, similarly to bacterial DNA, the non-methylated CpG sites of mtDNA, which activate innate immunity and inflammation, are likely to participate in the molecular mechanisms of disease. Thus, ccf-mtDNA may represent a powerful biomarker for disease screening and prognosis at early stage, although its biological role may extend to generating the neurobiology of disease. The present manuscript discusses recent experimental findings in relationship with clinical evidence comparing neuro-immunological features of neurodegenerative disorders with frankly neuro-infectious diseases.